The influence of spatial features and atmospheric conditions on African lion vocal behaviour. (April 2021) - Wijers, Matthew; Trethowan, Paul; du Preez, Byron; Chamaillé-Jammes, Simon; Loveridge, Andrew J.; Macdonald, David W.; Markham, Andrew
Abstract : Long-distance vocalization is a characteristic of African lion, Panthera leo, behaviour and is important for maintaining territorial boundaries as well as locating distant group members. Vocal signalling is, however, a flexible behaviour that involves varying costs and benefits depending on environmental, social and spatial factors. Motivated by previous data collection limitations, we developed a novel approach to investigate the influence of atmospheric conditions and animal home range geography on lion vocal behaviour using acoustic and accelerometer biologgers. To compensate for the short lifetime of the acoustic biologger, we trained a machine-learning model to detect lion roars from long-term acceleration signals which yielded over 500 nights of data from seven individual lions. Analysis of detected roar events revealed that vocalizations occurred mainly at night with a peak just before dawn. The relative likelihood of vocalization was negatively related to wind speed and temperature and positively related to absolute humidity suggesting that lions preferred to roar under conditions that reduce sound attenuation and thereby maximize calling area. Roar occurrence was found to be dependent on an animal's location relative to its home range with lions demonstrating an apparent avoidance for vocalizing beyond the home range boundary. Lions were also more likely to roar repeatedly while closer to rivers and water points within their home range. This study is the first of its kind and not only improves the understanding of lion vocal behaviour but can also inform new approaches for recording animal vocalizations remotely. Highlights: Acoustic accelerometer biologgers enable detection of lion roars from body movement. Lions vocalize mainly at night with a peak just before dawn. Roaring is preferred when temperature and wind speed are low and humidity is high. Lions avoid roaring beyond their home range boundary. Lions are more likely to roar repeatedly when closer to rivers and water points.